Analisis Sistem Klaim Jaminan Hari Tua Pada Tenaga Kerja Yang Mengundurkkan Diri Pada BPJS Ketenagakerjaan Cabang Padangsidempuan - Harahap, Lesti; Lubis, Fauzi Arif; Inayah, Nurul (Universitas Labuhanbatu, 2023)
To claim Old Age Security, workers who are participants must go through several stages of claiming old age security. The implementation of the Old Age Security (JHT) claim system at BPJS Employment Padangsidempuan Branch has several obstacles, one of which is the lack of understanding of participants regarding the JHT claim system which results in less effective use of the claims system provided by BPJS Employment. This research was conducted with the aim of finding out an overview of the Old Age Security (JHT) claim system for workers who have become Old Age Security (JHT) participants at BPJS Employment Padangsidempuan Branch. The data analysis technique used by the author is using a qualitative descriptive method using data reduction and data display analysis. Meanwhile, data collection techniques have been carried out through interviews and documentation. The results of this research show that the implementation of the old age insurance claim system at BPJS Employment Padangsidempuan Branch is generally not in accordance with existing regulations. This is based on participants not attaching a Certificate of Stopping Work or a Certificate of No Longer Working when making a claim. The use of the old age insurance claim system is less effective because many participants still make claims only at branch offices, even though apart from branch offices, participants can make claims through service points or online.